CSR Communication Strategies of Adira Finance to Increase the Corporate Reputation - Fransisca, Grafviella; Juliadi, Rismi (Universitas Dian Nuswantoro, 2024)
As one of the well-known financial companies in Indonesia, Adira Finance has a strategy for CSR communication to the stakeholders accordingly. This effort intends to increase the corporate reputation after the COVID-19 pandemic through a local creative festival program. This study aims to find out the Corporate Social Responsibility communication strategies of Adira Finance to increase the corporate reputation. This study uses the concept of CSR communication strategies of Mette Morsing and Majken Schultz and the concept of the reputation of Fombrun. The study uses descriptive qualitative with case study method and in-depth interviews as data collection techniques, and pattern matching techniques as data analysis. This study found that Adira Finance applies the stakeholder involvement strategy for CSR communication to enhance the company's reputation among internal and external stakeholders. Adira Finance has implemented four aspects of reputation and appropriate CSR communication strategy; therefore, it has received positive news sentiments regarding CSR awards from the private organizer and has an employee engagement rate of more than 90%.